Facile one-pot synthesis of silver nanoparticles encapsulated in natural polymeric urushiol for marine antifouling. Issue 24 (15th April 2020) - Zheng, Lu; Lin, Yucai; Wang, Donghui; Chen, Jipeng; Yang, Ke; Zheng, Binbin; Bai, Weibin; Jian, Rongkun; Xu, Yanlian
Abstract : PUL/AgNPs was developed by a one-step reaction, PUL/AgNPs coatings showed excellent antifouling performance in antimicrobial experiments and marine field tests. Abstract : Silver nanoparticle-based coatings have been regarded as promising candidates for marine antifouling. However, current toxic fabrication methods also lead to environment risks. Nanoparticle agglomeration, poor compatibility with polymer, and rapid release of Ag + result in short-term efficacy. In this study, a facile one-pot synthesis method of silver nanoparticles (AgNPs) encapsulated in polymeric urushiol (PUL) was developed. AgNPs were synthesized in situ by natural urushiol, serving as a reductant, dispersant and surfactant. Simultaneously, silver nitrate catalyzed the polymerization of urushiol into PUL. This in situ reduction method made AgNPs uniformly distributed in the polymer matrix. The binding between the AgNPs and the PUL resulted in the stable release of Ag + . Results showed the antibacterial rate of a 0.1% AgNPs coating is 100% in laboratory experiments. This environment-friendly coating showed good microbial inhibition performance with long-term (120 days) marine antifouling efficacy. This study shows the potential of preparing an eco-friendly coating with long-term marine antifouling ability.